THE ROLES OF SCHOOL ADMINISTRATORS IN THE VUCA WORLD AFFECTING THE APPLICATION OF DIGITAL TECHNOLOGY FOR TEACHING AND LEARNING IN SCHOOLS UNDER TRAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE - Chantacho, Surat; Nilkote, Reongwit; Boonloy, Waiwoot (Journal of MCU Nakhondhat, 2023)
The purposes of the research were to: 1) study the roles of school administrators in the vuca world of educational institutions under Trat Primary Educational Service Area Office, 2) study the application of digital technology for teaching and learning in schools under Trat Primary Educational Service Area Office, 3) study the relationship between the roles of school administrators in the vuca world and the application of digital technology for teaching and learning in schools under Trat Primary Educational Service Area Office and 4) Create a forecast for the roles of school administrators in the vuca world affecting the application of digital technology for teaching and learning in schools under Trat Primary Educational Service Area Office. The sample was a group of 302 teachers under the Trat Primary Educational Service Area Office, Academic Year 2022, The statistics used for analysis data were: mean, standard deviation, Pearson’s product moment correlation coefficient and multiple regression analysis. The results of the study were as follows : 1) the roles of the school administrators in the vuca world was at the high level overall and in all aspects, 2) the application of digital technology for teaching and learning in schools was at the highest level overall and in all aspects, 3) the roles of the school administrators and the application of digital technology for teaching and learning in schools, overall, had a moderate level of positive correlation, statistically significant at the .05 level, and 4) create a forecast for the roles of the school administrators in the vuca world affecting the application of digital technology for teaching and learning in schools to operational support, and modification and development of the structure. 19.10 percent of the application of digital technology for teaching and learning in schools, with statistical significant relationships at the .05 level, with a multiple correlation coefficient of .44. and a predictive power of .191. and create the forecasting equation in the form of raw scores, = 2.804 + 0.245 (X4) + 0.178 (X3) and the forecasting equation in the form of standard scores is = 0.269 (X4) + 0.206 (X3).